Ceny surowca drzewnego w warunkach klęsk żywiołowych w Nadleśnictwie Węgierska Górka - Sikora, Adam; Ukalska, Joanna (Leśne Prace Badawcze, 2014)
The aim of the study was to determine the impact of increased timber logging after natural disasters on timber assortments, unit prices, as well as average prices of timber spruce and total timber. The net sales prices of the years 2004-2010, available from the database of the State Forests Information System (SFIS) for the Forest District of Węgierska Górka, were analysed and compared to the prices of selected forest districts within the Regional Directorate of State Forests in Cracow (RDSF). The forest districts were classified based on the volume of logged timber leading to a separation into two groups of two and six forest districts. Moreover, we tested for significance in the linear trends of relevant characteristics and determined confidence intervals. Furthermore, we calculated the rate of growth (decrease) of the unit prices. Our studies show a decrease in price of only some of the timber assortments despite a significantly increased supply. Price declines were observed for the average prices of timber spruce and total timber due to their lowered quality. The price of timber assortments was mainly determined by effects of macroeconomic factors.